2012
DOI: 10.1099/mic.0.052118-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Trichoderma gene expression in interactions with tomato plants using high-density oligonucleotide microarrays

Abstract: Trichoderma spp. are widely used as biopesticides and biofertilizers to control diseases and to promote positive physiological responses in plants. In vitro and in vivo assays with Trichoderma harzianum CECT 2413 (T34), Trichoderma virens Gv29-8 (T87) and Trichoderma hamatum IMI 224801 (T7) revealed that these strains affected the growth and development of lateral roots in tomato plants in different ways. The early expression profiles of these Trichoderma strains were studied after 20 h of incubation in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 51 publications
1
54
1
2
Order By: Relevance
“…For the tomato hydroponic cultures (10,30,31), sterile tomato seeds were placed inside Phytatray II boxes (Sigma, St. Louis, MO) (30 seeds per box) on a sterile gauze sheet over a sterile stainless steel screen, which held them 1 cm above 100 ml of liquid MS medium, and maintained at 21°C in a plant growth chamber with controlled light and humidity conditions, as indicated above, for 2 weeks. Spores (10 6 ml Ϫ1 ) from the T34-5.27-b1 control strain, the T34-5.27-tri4.2 transformant, and, when indicated, strain B05.10, were used to inoculate 250-ml flasks containing 100 ml of CM medium.…”
Section: Methodsmentioning
confidence: 99%
“…For the tomato hydroponic cultures (10,30,31), sterile tomato seeds were placed inside Phytatray II boxes (Sigma, St. Louis, MO) (30 seeds per box) on a sterile gauze sheet over a sterile stainless steel screen, which held them 1 cm above 100 ml of liquid MS medium, and maintained at 21°C in a plant growth chamber with controlled light and humidity conditions, as indicated above, for 2 weeks. Spores (10 6 ml Ϫ1 ) from the T34-5.27-b1 control strain, the T34-5.27-tri4.2 transformant, and, when indicated, strain B05.10, were used to inoculate 250-ml flasks containing 100 ml of CM medium.…”
Section: Methodsmentioning
confidence: 99%
“…T. parareesei-tomato hydroponic cultures were carried out as previously described (15). Briefly, T6 was cultured in minimal medium (MM) (30) containing 2% glucose at 28°C with stirring for 48 h. The mycelium was then collected, washed, and used to inoculate Phytatray II boxes (Sigma-Aldrich, Madrid, Spain) containing 2-week-old tomato plants in Murashige-Skoog (MS) medium (Duchefa Biochemie BV, Haarlem, The Netherlands) supplemented with 1% (wt/vol) sucrose, pH 5.7.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Trichoderma strains are also able to stimulate defense responses in plants, inducing resistance to biotic and abiotic stresses, and to promote plant growth (5)(6)(7). Several studies have reported the responses of plants to the presence of a rootcolonizing Trichoderma biocontrol strain (8)(9)(10)(11)(12), and investigations describing the Trichoderma transcriptomic changes elicited by plants using macroarray (13,14) and microarray (15,16) analyses have been performed with biocontrol species.…”
mentioning
confidence: 99%
“…Tomato-Trichoderma hydroponic cultures were carried out as previously described (45). First, sterile tomato seeds were placed inside Phytatray II boxes (Sigma, St. Louis, MO) (30 seeds per box) on a sterile gauze sheet over a sterile stainless steel screen, which held them 1 cm above 100 ml of Murashige and Skoog (MS) medium (Duchefa, Netherlands), and maintained at 25°C in a plant growth chamber with controlled light and humidity, as described above, for 2 weeks.…”
Section: Methodsmentioning
confidence: 99%